Pathognomonic macular ripples are revealed by polarized infrared retinal imaging. Issue 20 (October 2021) - Ansari, Darius; Borkar, Poulami P; Davis, Patricia L; Collison, Frederick T; Wynne, Niamh; Zangler, Nicole; Fishman, Gerald A; Carroll, Joseph; Yao, Xincheng; Grassi, Michael A
A pathognomonic macular ripple sign has been reported with scanning laser ophthalmoscopy images in patients with foveal hypoplasia, though the optical basis of this sign is presently unknown. Here we present a case series of seven individuals with foveal hypoplasia (based on spectral domain optical coherence tomography). Each patient underwent infrared scanning laser ophthalmoscopy retinal imaging in both eyes, acquired with and without a polarization filter and assessment for a ripple-like effect in the fovea. On imaging, macular ripples were present in all eyes with foveal hypoplasia when using a polarization filter, but not when imaged without the filter. We conclude that the macular ripple sign is an imaging artifact attributable to the unique pattern of phase retardation of the Henle fiber layer in the setting of foveal hypoplasia. By utilizing a polarization filter with retinal photography, this feature can be exploited to promptly identify foveal hypoplasia in settings where OCT is not possible due to nystagmus.